Effects of heterogeneous surface geometry on secondary flows in turbulent boundary layers. (10th March 2020) - Medjnoun, T.; Vanderwel, C.; Ganapathisubramani, B.
Abstract : Abstract : The effect of spanwise heterogeneous surface geometry on turbulent boundary layer secondary flows and on skin friction is investigated experimentally. The surfaces consist of smooth streamwise-aligned ridges of different shapes and widths with spanwise wavelengths comparable to the boundary layer thickness ( S/[STIX]x1D6FF≈ O(1) ). Cross-stream stereoscopic particle image velocimetry combined with oil-film interferometry is used to investigate the flow field and assess the drag. Results show that the spanwise distribution of the skin friction varies as a consequence of the mean flow heterogeneity and is highly dependent on surface geometry. The swirling strength maps revealed remarkable changes in the secondary flow structures for different ridge shapes. For wide ridges, topological changes occur showing the appearance of tertiary vortices coexisting with the large-scale secondary structures. An imbalance in favour of these tertiary structures occurs over a certain width which take over the secondary structures, causing a swap in the locations of the low- and high-momentum pathways. Furthermore, the results indicate that the spanwise spacing alone is insufficient to characterise the surface heterogeneity. A new parameter ( [STIX]x1D709 ), which is based on the ratio of the perimeter over and below the mean surface height, is shown to adequately capture the changes in skin friction and streamwise circulation of the secondary motions. Triple decomposition allowed the quantification of the dispersive stresses for all these cases, which can contribute up to 55 % of the total shear stress when strong secondary motions occur.